The Monetary Situation in the United States, as Viewed from Without - Lehfeldt, R. A. (Quarterly Journal of Economics, 1927)
Amount of bank deposit currency liable to disturbance from savings deposits, 26. — Initiative in expansion from saving and borrowing respectively, 28. — The features of a monetary expansion, 29. — Circulating and fixed capital as basis for money, 31. — The dispersion of prices, 32. — The appropriate price index, 33. — The facts of recent history, 35. — Prospects, 37.